(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
The aim of the article is to conduct a comprehensive study on the ways and means for improving intra-school supervision (ISS) in public educational institutions. ISS, which is directed at enhancing the effectiveness of the educational process, resource management, and the professional development of teachers, plays a significant role in improving the quality of education. Intra-school supervision should be implemented using a systematic methodological approach, which will help identify shortcomings in processes and ways for their elimination and correction. The relevance of the article is based on the results of recent reforms in the field of public education, which often do not include improvements to ISS mechanisms. The scientific novelty lies in the development of a comprehensive ISS system that should encompass all educational levels and directions. This system will help increase the efficiency of educational institutions and ensure the improvement of education quality by focusing on the evaluation and monitoring of educational processes. The research findings are substantiated by surveys, which reveal that a significant portion of educational institution staff lacks a clear understanding of the content and objectives of ISS implementation. This indicates that the current process often has a formal nature and cannot ensure the necessary supervision. Therefore, new approaches and strategies are needed to elevate the management level of ISS. It is necessary that the ISS process is based on democratic and collaborative principles, which will enhance transparency and accountability. The article proposes solutions that include proper resource management, clear definitions of responsibilities and functions, the active involvement of participants in the educational process as well. This system can serve as a good example for educational institutions that aim to improve their ISS processes. Enhancing effectiveness will be possible only through the implementation of appropriate steps and reforms that engage all stakeholders at all educational levels, minimizing formality and creating an effective and sustainable learning environment that fosters the professional development of teachers and improves the quality of students’ knowledge.